Molecular characterization of a novel cytorhabdovirus with a unique genomic organization infecting yerba mate (Ilex paraguariensis) in Argentina - Bejerman, Nicolas Esteban (2020)
The genome of a novel rhabdovirus was detected in yerba mate (Ilex paraguariensis St. Hil.). The newly identified virus, tentatively named "yerba mate virus A" (YmVA), has a genome of 14,961 nucleotides. Notably, eight open reading frames were identified in the antigenomic orientation of the negative-sense, single-stranded viral RNA, including two novel accessory genes, in the order 3′-N-P-3-4-M-G-L-8-5′. Sequence comparisons of the encoded proteins as well as phylogenetic analysis suggest that YmVA is a new member of the genus Cytorhabdovirus, family Rhabdoviridae. YmVA's unique genomic organization and phylogenetic relationships indicate that this virus likely represents a distinct evolutionary lineage among the cytorhabdoviruses.